2005
DOI: 10.1089/ars.2005.7.1612
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Phorbol Ester-Induced Up-Regulation of Cyclooxygenase-2 and Matrix Metalloproteinase-9 by Blocking ERK1/2 Phosphorylation and NF-κB Transcriptional Activity in MCF10A Human Breast Epithelial Cells

Abstract: Elevated levels of cyclooxygenase-2 (COX-2) and matrix metalloproteinases (MMPs) are often observed in various types of cancerous and transformed cells, and hence recognized as potential molecular targets for the chemoprevention. In the present study, we investigated the possible inhibitory effects of curcumin on the expression of COX-2 and MMP-9 induced by the tumor promoter 12-O-tetradecanoylphorbol 13-acetate (TPA) in MCF10A human breast epithelial (MCF10A) cells and the underlying mechanisms. Curcumin inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…The H-Ras WB cells were developed from the transfection of WB cells with a retroviral vector containing the v-Ha-ras oncogene and a neomycin-resistant marker. 19 Cells (at passages [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] were cultured in modified Eagle's medium supplemented with 5% fetal bovine serum and penicillin/streptomycin at 37°C in a humidified atmosphere of 5% CO 2 and 95% air.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The H-Ras WB cells were developed from the transfection of WB cells with a retroviral vector containing the v-Ha-ras oncogene and a neomycin-resistant marker. 19 Cells (at passages [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] were cultured in modified Eagle's medium supplemented with 5% fetal bovine serum and penicillin/streptomycin at 37°C in a humidified atmosphere of 5% CO 2 and 95% air.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…We examined the activation of transcription factors NF-jB and AP-1, which have been shown to regulate the expressions of MMP-9 and COX-2, [13][14][15] by performing an EMSA using nuclear extracts of WB and H-Ras WB cells. The DNA binding activity of NF-jB was markedly increased in H-Ras WB cells compared to WB cells (Fig.…”
Section: Cox-2 Is Required For the H-ras-induced Invasive And Migratimentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by our group has shown that curcumin is able to sensitize lung cancer cells to undergo anoikis through a mechanism that involves post-translational modification of Bcl-2 via the ubiquitin-proteasome pathway (Pongrakhananon et al, 2010). Curcumin also acts as a negative regulator of cancer cell migration and invasion through diverse signaling pathways including MMP-9, MMP-2 and COX-2 (Philip et al, 2004, Lee et al, 2005Hong et al, 2006;Lin et al, 2009). Animal and clinical studies of curcumin have been well investigated.…”
Section: Fig 1 Anticancer Properties Of Curcuminmentioning
confidence: 99%
“…The treatment of DU145 prostate cancer cells with curcumin, an anti-metastatic derivative from tumeric, has been shown to decrease the levels of MMP-2 and -9 and lead to a decrease in tumor volume [79]. Curcumin treatment has also been shown to alter the invasive and metastatic properties of MCF10A human breast epithelial cells [80] and decrease metastasis to lung in a human breast cancer xenograft model [81] by decreasing the levels of MMP-9 and COX-2. According to Eiseler, et al, highly invasive breast cancer human tissue samples, regardless of stage and progesterone or estrogen dependence, were shown to have reduced Protein Kinase D1 (PKD1) expression in greater than 95% of the tumor samples compared to normal breast tissue [82].…”
Section: Introductionmentioning
confidence: 99%